2000
DOI: 10.1128/jvi.74.12.5525-5533.2000
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Stimulates Liver Macrophages To Release Mediators That Inhibit an Early Step in Hepadnavirus Replication

Abstract: Hepadnaviruses are known to be sensitive to various extracellular mediators. Therefore, bacterial endotoxin, which induces the secretion of proinflammatory mediators in the liver, was studied for its effect on hepadnavirus infection in vitro using the duck hepatitis B virus (DHBV) model. In initial experiments, endotoxin was shown to inhibit DHBV replication in primary duck hepatocyte cultures prepared by standard collagenase perfusion. As a primary endotoxin target, hepatic nonparenchymal cells (NPC) contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…In contrast, the amount of the HBV transgene, which serves as a transcription template to initiate HBV replication, as well as HBV transcripts remained unaffected, indicating that HBV replication is blocked by IFNg at a posttranscriptional step. 48,49 Low doses of Dox (0.3 mg/ml) were sufficient to induce IFNg expression and to block HBV replication, and even 10-fold higher doses (3 mg/ ml) had no additional effects. Since the addition of Dox to the drinking water was the only difference between mice in the 'on' and in the 'off' state, and since a treatment with Dox alone had no effect on HBV replication, the drastic effect on HBV replication was clearly due to IFNg expression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the amount of the HBV transgene, which serves as a transcription template to initiate HBV replication, as well as HBV transcripts remained unaffected, indicating that HBV replication is blocked by IFNg at a posttranscriptional step. 48,49 Low doses of Dox (0.3 mg/ml) were sufficient to induce IFNg expression and to block HBV replication, and even 10-fold higher doses (3 mg/ ml) had no additional effects. Since the addition of Dox to the drinking water was the only difference between mice in the 'on' and in the 'off' state, and since a treatment with Dox alone had no effect on HBV replication, the drastic effect on HBV replication was clearly due to IFNg expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the addition of lipopolysaccharides (LPS, endotoxin) to PDH cultures inhibited DHBV replication efficiently [98] . This was due to the release of interferon alpha and gamma from non-parenchymal cells (i.e.…”
Section: In Vitro Infectionmentioning
confidence: 99%
“…To be able to clearly distinguish between adsorption or unspecific uptake of HBV and infection of DC by HBV, we took advantage of recently developed HBVbased vectors. 17 Recombinant HBV allow us to unambiguously assay the early steps of HBV infection 18 because of their ability to express luciferase after successful uptake and nuclear transport. 19 In addition, we investigated the formation of nuclear HBV cccDNA after infection with wild-type HBV.…”
Section: H Epatitis B Virus (Hbv) Infection Represents Amentioning
confidence: 99%